'And if we don't stop him, I don't know who will': recoding intimacy in My Dad Wrote a Porno. Issue 2 (3rd April 2022) - Euritt, Alyn; Korfmacher, Anne
ABSTRACT: Intimacy is emerging as a central concept in podcast studies. Where much of this research asks what intimacy reveals about podcasting, we ask what podcasting can teach us about intimacy. To this end, we analyze My Dad Wrote a Porno, a show revolving around host Jamie Morton reading the erotic Belinda Blinked series while co-hosts Alice Levine and James Cooper react. We argue that the podcast creates intimacy through its live commentary and its associations with friendship and domesticity. The podcast differentiates these forms of intimacy from the familial and erotic constructions it links to Belinda Blinked, separating the novel's sexual constructions from its community and positioning them as in need of recoding and translation. Instead of intimacy being an inherent part of podcasting, then, we show how My Dad Wrote a Porno juggles different forms of the construct to negotiate its specific approach to intimacy.